OPTIMALISASI PEMBELAJARAN IPA MELALUI PENGUATAN LITERASI DIGITAL SISWA SEKOLAH DASAR - Trivena; Susanna Vonny Noviana Rante (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid advancement of digital technology has increased elementary school students' access to gadgets. However, their use remains predominantly focused on non-educational activities, limiting their potential contribution to the learning process. This condition was also identified at UPT SDN 2 Kurra, Tana Toraja Regency, where students had not yet utilized gadgets effectively to support science learning. This community service program aimed to optimize science learning by strengthening students' digital literacy through education on the responsible use of gadgets. The program was conducted on June 11, 2026, using a Participatory Action Approach (PAA) involving 42 fourth- and fifth-grade students and 13 teachers. The activities consisted of digital wellbeing education for students through the implementation of the 20-20-20 rule and the "Digital Hero Pledge," as well as a teacher workshop on integrating QR Code-based science e-modules and virtual laboratory simulations into classroom instruction. Program evaluation was carried out through classroom observations, educational quizzes, teacher performance demonstrations, and post-activity behavioral monitoring. The results showed that 95% of the students were able to explain the principles of responsible gadget use and the 20-20-20 rule, while approximately 83% successfully practiced the simulation independently. All participating teachers were able to operate the QR Code-based e-modules and integrate them into science instruction. In addition, a shared commitment among teachers, students, parents, and the school community was established through the "Digital Hero Pledge" to promote healthy and productive gadget use. These findings indicate that strengthening students' digital literacy, combined with enhancing teachers' digital pedagogical competencies, can transform gadgets from entertainment devices into effective learning tools that support the optimization of science learning in elementary schools